PERADABAN ISLAM DI SPANYOL DAN PENGARUHNYA TERHADAP PERADABAN BARAT - El-Haji, Ubadah (Institut Agama Islam Negeri (IAIN) Palu, 2008)
Spain or Andalusia in the context of classical Islam was one of the provinces of Umayyah Dynasty I or Eastern Amawiyyah. Then it turned into an autonomy dynasty called Daulah Bani Umayyah II or Western Umayyah and separated from Abbasiyyah Dynasty. In the matter of education and science/knowledge development, Western Amawiyyah had been succeeded in competing the brightness of Abbasiyyah Dynasty of Baghdad. Philosophy, science encompassing medicine, surgery, pharmacy, astronomy, mathematics, chemistry, music, etc. were developed at this time. The influence of Islamic sciences on Europe and Western countries had been lasting since 12th A.D century, and brought about the reawakening movement (renaissance) in Europe at 14th A.D century through the Arabic language translations into Latin language.Kata Kunci: peradaban Islam, perdaban Barat, Dinasti Umayyah, Dinasti Abbasiyyah, pendidikan, ilmu pengetahuan